2022
DOI: 10.1002/cam4.4740
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cirrhosis on long‐term survival outcomes of patients with intrahepatic cholangiocarcinoma

Abstract: Background:The correlation between cirrhosis and the long-term oncological outcome in intrahepatic cholangiocarcinoma (ICC) is debatable, and this study aimed to explore the impact of cirrhosis on the long-term prognosis of patients with ICC. Methods: A total of 398 ICC patients were identified in the Surveillance, Epidemiology, and End Results (SEER) database from 2000 to 2018. The diagnosis of cirrhosis was based on the Ishak fibrosis score provided by the SEER database. Propensity score matching (PSM) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The HR of cirrhosis in our research is higher than 1, suggesting that cirrhosis itself is a risk factor, which was consistent with ndings by Wang J et al(2) and Wei T et al (14). Comparable long-term survival was acquired between cases with cirrhosis and those without cirrhosis even after matching, suggesting that the survival impact of cirrhosis is limited among IHCC cases and the actual factors determining the overall prognosis is the tumor stage, which has also been validated in previous publications (2,14).…”
Section: Propensity Score Matching Analysessupporting
confidence: 92%
See 2 more Smart Citations
“…The HR of cirrhosis in our research is higher than 1, suggesting that cirrhosis itself is a risk factor, which was consistent with ndings by Wang J et al(2) and Wei T et al (14). Comparable long-term survival was acquired between cases with cirrhosis and those without cirrhosis even after matching, suggesting that the survival impact of cirrhosis is limited among IHCC cases and the actual factors determining the overall prognosis is the tumor stage, which has also been validated in previous publications (2,14).…”
Section: Propensity Score Matching Analysessupporting
confidence: 92%
“…For patients with liver malignancies, cases with cirrhosis often could only tolerate a smaller range of surgical resection, share a lower chance of achieving the clear surgical margin, and therefore share a poorer prognosis. The signi cance of cirrhosis in cases with IHCC has been systematically evaluated by Wang J et al based on the public Surveillance, Epidemiology, and End Results (SEER) database (2). Their results indicated that cirrhosis was not associated with a worse prognosis in cases with IHCC even after propensity score matching (PSM) (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation